PENGARUH PARTISIPASI ANGGARAN PADA KINERJA UNIVERSITAS APTIK YANG DIMEDIASI OLEH TRUST PEGAWAI - Almatius Setya Marsudi (Fakultas Ekonomi Universitas Pekalongan, 2019)
This study aims to examine the effect of budget participation on task performance with trust as intervening variables in the organization. The population is drawn from 17 universities in the APTIK environment in Indonesia. Path analysis is use to see whether trust is a intervening variable in the effects of budget participation on task performance. The Research finding is the budget participation influence on task performance but there is no role of trust as intervening variable the effect on budgeting participation influence on task performance. Keywords: Budget Participation, Task Performance, Trust, Mediation